2020
DOI: 10.1057/s41599-020-00601-z
|View full text |Cite
|
Sign up to set email alerts
|

Concepts for historical and geographical thinking in Sweden’s and Spain’s Primary Education curricula

Abstract: The goal of this study is to compare the presence of concepts for historical and geographical thinking in the national curricula for Primary Education in Spain and Sweden in order to analyze if these thinking concepts can enable new active learning methodologies in the Social Science classroom. The comparative study is based on a qualitative investigation using a horizontal evaluation instrument (international compared analysis). Compared items were divided in four dimensions: 1. curriculum structure—subjects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The majority consider heritage to consist of important monuments and buildings, while other heritage elements pass by unnoticed in classrooms and lose their didactic potential. For this reason and the lack of concepts for historical thinking, some authors, such as González-Monfort [41] or Moreno-Vera and Alvén [44], advocate the inclusion of heritage education from the earliest educational stages, beginning in early-childhood education.…”
Section: Discussionmentioning
confidence: 99%
“…The majority consider heritage to consist of important monuments and buildings, while other heritage elements pass by unnoticed in classrooms and lose their didactic potential. For this reason and the lack of concepts for historical thinking, some authors, such as González-Monfort [41] or Moreno-Vera and Alvén [44], advocate the inclusion of heritage education from the earliest educational stages, beginning in early-childhood education.…”
Section: Discussionmentioning
confidence: 99%
“…This approach aimed to foster greater student engagement in their own teaching-learning process, promoting self-management and awareness of their knowledge. This line of action is aligned with current issues of geography education [17,19,20]. Concurrently, this approach provided teachers with daily information of interest about the learning process, eliminating the need to wait for summative assessments for this information [8,9,40].…”
Section: Discussionmentioning
confidence: 86%
“…As various authors such as Wineburg [16] point out, information is now just a few mouse clicks away. Therefore, the importance lies not just in knowing the information contained in a textbook, but in understanding how to access it and competently judge its veracity [17,18]. In fact, Brooks et al [19] underscore the need for students to think geographically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This can basically be explained by the fact that the teaching of the social sciences, and history in particular, still maintains an extremely rigid and traditional structure ( Estepa, 2017 ; Moreno-Vera and Alvén, 2020 ), in which the explanatory method (the masterclass) continues to be the most common approach when constructing new knowledge. The textbook is still the most commonly used educational resource in history classes, as pointed out by Vera et al (2014) , who, following an investigation of history teaching in Spain, concluded that more than 85% of teachers continued to employ textbooks as the only resource in the classroom.…”
Section: Discussionmentioning
confidence: 99%